2019
DOI: 10.1002/gcc.22820
|View full text |Cite
|
Sign up to set email alerts
|

The anaphase‐promoting complex: A key mitotic regulator associated with somatic mutations occurring in cancer

Abstract: The anaphase‐promoting complex/cyclosome (APC/C) is an E3 ubiquitin ligase that helps control chromosome separation and exit from mitosis in many different kinds of organisms, including yeast, flies, worms, and humans. This review represents a new perspective on the connection between APC/C subunit mutations and cancer. The complex nature of APC/C and limited mutation analysis of its subunits has made it difficult to determine the relationship of each subunit to cancer. In this work, cancer genomic data were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 202 publications
0
12
0
Order By: Relevance
“…CDH1 and CDC20 have tumor suppressor function and oncogenic function, respectively (7)(8)(9). Although many studies have shown that CDC27 mutations are detected in various cancer specimens, the role of CDC27 in cancer is uncertain, especially in lymphoma (10).…”
Section: Introductionmentioning
confidence: 99%
“…CDH1 and CDC20 have tumor suppressor function and oncogenic function, respectively (7)(8)(9). Although many studies have shown that CDC27 mutations are detected in various cancer specimens, the role of CDC27 in cancer is uncertain, especially in lymphoma (10).…”
Section: Introductionmentioning
confidence: 99%
“…Although the low variance filtering removed many previously selected features, it selected two new gene expression features, ANAPC16 and TIMM23 which were not selected by any other method. The TIMM23 gene has been shown to be downregulated for Endometriosis [ 41 ], and ANAPC16 has potentially higher rates of alterations in certain cancers [ 42 ]. PTEN and KLLN genes are both associated with endometrial cancers [ 43 ], and SuMO-Fil retained one of the DNA methylation feature selections ( cg08859916 ) corresponding to those genes that were also selected in the unfiltered data.…”
Section: Resultsmentioning
confidence: 99%
“…CDC27 is one of the main components of the anaphase-promoting complex/cyclosome and overexpression and variations in CDC27 expression may affect the cell cycle, mitosis, cancer pathogenesis and prognosis [ 60 , 61 ]. Thus far, there is no specific targeted therapy for CDC27 .…”
Section: Discussionmentioning
confidence: 99%